Customer satisfaction and switching intentions of banking services end-users in Montenegro - Milorad Jovović; Nikola Mišnić; Bojan Pejović; Marija Mijušković (Journal of Central Banking Theory and Practice, 2023)
Numerous research studies of the various companies' business practices indicate a strong relationship between customer satisfaction, as an overall positive response generated after the use of the specific product or service, and their intention to continue using the products/services of the company. As a rule, satisfied and particularly delighted customers show intention to return and become loyal, whereas dissatisfied and disappointed customers have switching intentions. Therefore, the objective of this study is to empirically test to which extent the intention to switch banks in Montenegro depends on customer satisfaction or dissatisfaction. With this regard, we have posed a question inquiring about the level of consumers satisfaction/dissatisfaction with banking services in Montenegro, what their intentions are regarding the continuation of using services of the chosen bank (customer retention & defection), and to what extent customer satisfaction and dissatisfaction determine their intention to change the bank. The analysis has established a statistically significant correlation between satisfaction, dissatisfaction, and intentions of leaving the bank. Findings has shown a relatively high level of customer satisfaction with banking services in Montenegro, as well as confirming that dissatisfaction usually leads to the intention to leave and change the bank, while satisfaction leads to the continued use of the bank's services. A high level of competition in the banking services market as well as the struggle for each consumer makes this topic undeniably current and this research represents a significant input for the bank management in Montenegro regarding the identification of the real situation with customer satisfaction and their intention to switch banks in accordance with their level of satisfaction.
Keywords: M39; G20; 330; Customer satisfaction; Switching intentions; Customer retention; Customer defection; banking